Section 2: Selection, Procurement and Distribution 2019
DOI: 10.1136/ejhpharm-2019-eahpconf.53
|View full text |Cite
|
Sign up to set email alerts
|

2SPD-013 Economic impact of the use of flat dose vs personalised dose of pembrolizumab

Abstract: ConclusionThe pharmaceutical process with the highest productivity was elaboration of cytotoxic drugs. The processing of EA vs 'off-label' in oncology means 92.4% of total management activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…However, pembrolizumab was hampered by its extremely high cost [21]. Moreover, the SD was reported to lead to unnecessary dose and economic impacts in patients who were a standard weight [22][23][24]. Goldstein et al showed that a pembrolizumab dose reduction strategy could save approximately 24.0% of the annual cost, compared with the cost of the 200 mg fixed dose [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, pembrolizumab was hampered by its extremely high cost [21]. Moreover, the SD was reported to lead to unnecessary dose and economic impacts in patients who were a standard weight [22][23][24]. Goldstein et al showed that a pembrolizumab dose reduction strategy could save approximately 24.0% of the annual cost, compared with the cost of the 200 mg fixed dose [23].…”
Section: Introductionmentioning
confidence: 99%